2021
DOI: 10.1101/2021.05.06.443016
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ongoing neural oscillations predict the post-stimulus outcome of closed loop auditory stimulation during slow-wave sleep

Abstract: The large slow oscillation (SO, 0.5-2Hz) that characterises slow-wave sleep is crucial to memory consolidation and other physiological functions. Manipulating slow oscillations can enhance sleep and memory, as well as benefitting the immune system. Closed-loop auditory stimulation (CLAS) has been demonstrated to increase the SO amplitude and to boost fast sleep spindle activity (11-16Hz). Nevertheless, not all such stimuli are effective in evoking SOs, even if they are precisely phase-locked. Here, we studied … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…This hypothesis further suggests the existence of some nonexplicit cortical conditions that determine cortical sensitivity to the stimulation (i.e., whether the stimulation would boost SOs dynamics, whether it would be completely ineffective, or even induce awakenings). In line with this hypothesis, recent analyses suggest that the amplitude of SO peaks may facilitate global synchronization of post-neuronal down-states, thereby enhancing the amplitudes of the resulting slow wave troughs (Navarrete et al, 2022;Torres et al, 2021;Wei et al, 2020). Congruently, we found that large and synchronous C1 and C3 events were increased by stimuli during large peaks of the SOs (with average amplitudes larger than +40 μV across all EEG channels, Figures 2e & 2f).…”
Section: Changes On Slow Wave Categories Induced By Clasmentioning
confidence: 85%
See 1 more Smart Citation
“…This hypothesis further suggests the existence of some nonexplicit cortical conditions that determine cortical sensitivity to the stimulation (i.e., whether the stimulation would boost SOs dynamics, whether it would be completely ineffective, or even induce awakenings). In line with this hypothesis, recent analyses suggest that the amplitude of SO peaks may facilitate global synchronization of post-neuronal down-states, thereby enhancing the amplitudes of the resulting slow wave troughs (Navarrete et al, 2022;Torres et al, 2021;Wei et al, 2020). Congruently, we found that large and synchronous C1 and C3 events were increased by stimuli during large peaks of the SOs (with average amplitudes larger than +40 μV across all EEG channels, Figures 2e & 2f).…”
Section: Changes On Slow Wave Categories Induced By Clasmentioning
confidence: 85%
“…Presumably, CLAS might only enhance SO-SS-SWR coupling when the stimulus is able to increase the corticothalamic coordination of SW troughs which then sustain the co-occurrence of cortical down-states in the thalamus (Navarrete et al, 2020b;Todorova and Zugaro, 2020). Indeed, the capability of enhancing this corticothalamic coordination may not only lie in the effect of the stimulation, but also in the ongoing dynamics of the cortical activity during the CLAS click (Navarrete et al, 2022(Navarrete et al, , 2020a. However, currently it is not clear how the stimulus disturbs the ongoing neuronal dynamics and the characteristics of the resulting post-stimulus SW.…”
Section: Introductionmentioning
confidence: 99%